Validation and Application of the Positive Play Scale Adapted for Chinese Gamblers: Its Relation to Disordered Gambling and Gambling Attitudes - Tong, Kwok Kit; Chen, Juliet Honglei; Wu, Anise M. S. (Frontiers in Psychology, 2020)
Positive Play Scale (PPS) was designed to track the effectiveness of responsible gambling (RG) policy with a focus on positive changes on beliefs and behaviors instead of the absence of problem gambling symptoms. The current study aims to 1) validate PPS using a probability Chinese community sample in Macao, 2) explore the relations between PPS and gambling disordered gambling (GD) symptoms, and 3) evaluate the effects of gambling attitudes on PPS. Through two-step random sampling procedure, we interviewed 1002 locally dwelling Macao Chinese adults (44.3% males; Mage = 44.28 years, SDage = 17.35 years) by phone, in which 237 were past-year gamblers (49.8% males; Mage = 40.76 years, SDage = 15.78 years. Results showed that a two-dimension structure was acceptable for both PPS Beliefs scale and PPS Behaviors scale with reasonable model fit among gamblers. In addition to the satisfactory internal consistencies, the convergent validity PPS was also supported by its significant association with RG self-efficacy. All the PPS constructs were negatively correlated with GD symptoms while two PPS Behavior constructs significantly explained GD symptoms with negative valence. All the gambling attitude dimensions were also related to at least one PPS construct. The current study is the first study to validate PPS on a probability Chinese community sample and extended its generalization and applicability from online recruited gamblers to general community gamblers. The findings support PPS as a reliable and valid tool of assessing changes of positive play, which are associated with higher fewer gambling disorder symptoms. Further, the significant associations between gambling attitudes and PPS provide insights for future design and implementation for RG strategies.